The role of educational choice in occupational gender segregation: evidence from Trinidad and Tobago - Sandra Sookram; Eric Strobl (Institute for the Study of Labor (IZA), 2008)
We analyse the role of educational choice on the degree of occupational segregation in Trinidad and Tobago during a period in which educational policies intent on equating gender opportunities in education were implemented. To this end we utilise waves of the Trinidad and Tobago labour force survey over the period 1991-2004. Our results show that while educational segregation has fallen substantially over our sample period, this has not translated into less occupational segregation. This suggests that the educational policy has not been sufficient to combat occupational segregation. However, results at a more disaggregated level show that experiences have been heterogeneous across educational and occupational groups.
urn:nbn:de:101:1-20080619264
Keywords: I21; 370; Educational choice; occupational segregation; gender; Bildungsverhalten; Geschlecht; Frauenpolitik; Berufswahl; Segregation; Trinidad und Tobago